Algae and oxygen, humans and carbon: A Precambrian analogue for the Anthropocene. (April 2019) - Carson, James Taylor
In 2003 Paul Crutzen and Will Steffen asserted that across Earth's 4.5-billion-year history no analogue could be found for the Anthropocene. An analogue can, however, be located in the dim Precambrian past when, through oxygenic photosynthesis, cyanobacteria produced enough oxygen to alter the composition and character of the Earth System. The 'Great Oxygenation Event' that followed wiped out much of Earth's anaerobic life while giving rise to all subsequent aerobic life. It also offers a clear comparison with the Anthropocene that implicates how we think about our current predicament.